Legal Guarantee of Confidentiality of Customer Data in Online Loan Business Services - Ahmad Sahroni; Faisal Santiago; Ahmad Redi (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
ABSTRACT Fintech emerged along with changes in people's lifestyles which are currently dominated by users of information technology and the demands of a fast-paced life. Personal data and consumer behavior are part of big data whose economic value can be high, and vulnerable to The Ministry of Communication and Information (Kominfo), OJK, and the police in supervising online loan services. Customer data protection is regulated in Ministerial Regulation (Permen) Number 20 of 2016 concerning Personal Data Protection.